Pengaruh Penggunaan Metode Lactic Acid-Sucrose dengan Microwave Assisted Extraction (MAE) terhadap Polifenol Total dari Herba Suruhan (Peperomia pellucida (L.) Kunth) - Kharisma Ayu Tandi Datu; Nurul Fitriani; Islamudin Ahmad (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2019)
This study aim to determine the effect of use lactic acid and sucrose with assistance of Microwave Assisted Extraction (MAE) on Total Polyphenols from Herbs Suruhan (Peperomia pellucida (L.) Kunth). The dried sample of Herbs Suruhan was extracted using (green solvent) lactic acid-sucrose with a ratio of 1:1 g/g, 2:1 g/g and 3:1 g/g and the extraction conditions microwave strength was 50% for 10 minutes at a ratio sample and solvent 1:10 g/ml. Then the extract solution obtained to determine the total polyphenol level using the Folin Ciocalteu reagent and it absorbance was measured using a UV-VIS spectrophotometer at a wavelength of 791 nm. Based on the result of the study, obtained levels of polyphenols from each solvent condition used on the sample were 573,443 mg GAE/g (2:1), 472,479 mg GAE/g (1:1) and 420,14 mg GAE/g (3:1). It can be concluded that the lactic acid-sucrose method with microwave assisted extraction can be used to extract polyphenol compounds from Herbs Suruhan.